ONE ISLAMIC CULTURE, ONE POLITICAL SYSTEM, TWO FACES OF ISLAMIC POLITICS IN MADURA (JOURNAL OF INDONESIAN ISLAM, 2023)
The same culture and political system do not always give birth to twin political faces. This article finds that there are different policy formulations from the same cultural background and political system. Through a comparative study in two regencies, Sumenep and Pamekasan, in Madura, East Java, this article presents the results of qualitative research which shows that the existence of the same religious culture and the same political system gave birth to different Islamic political policies. There is a tendency to formalize Islam in one area (Pamekasan) and strengthen the substantive side of Islamic teachings in another area (Sumenep). Cultural similarities that are based on values, beliefs, and orientations as the dominant factors that influence political behavior, as well as the similarity of the system that places democratic mechanisms as a determinant factor for the birth of political output, have resulted in different policy formulations.